Seasonal Variations in Ocular Axial Length Increase among Children in the Czech Republic - Lenka Hecova; Stepan Rusnak; Vaclav Salcman; Jiri Cendelin (Journal of Ophthalmology)
In recent decades, the prevalence of myopia has increased worldwide as well as in European countries, and it has become an important medical and socioeconomic problem. Our prospective single-center study analysed the changes in ocular axial length (AXL) in a population of Central European schoolchildren from 2016 to 2019. The study included 528 eyes of 264 children with a mean age of 12.2 years at the beginning of the study. Visual acuity, ocular AXL, anterior chamber depth, and the questionnaire were examined at 6-month intervals (in spring and autumn, following the winter and summer periods, respectively). The average ocular AXL was 23.329 mm (median: 23.315 mm) at the beginning of the study and 23.525 mm (median: 23.505 mm) at the end of the study. The change in ocular AXL per month was significantly higher (p<0.0001) during the winter period (average: 0.013 mm, median: 0.011 mm) than during the summer period (average: −0.001 mm, median: 0.000 mm). We observed a significantly higher increase in ocular AXL in a Caucasian population during the winter period (with lower daylight exposure) than the summer period.